Linear Regression Analysis to predict the number of deaths in India due to SARS-CoV-2 at 6 weeks from day 0 (100 cases - March 14th 2020). Issue 4 (July 2020) - Ghosal, Samit; Sengupta, Sumit; Majumder, Milan; Sinha, Binayak
Abstract: Introduction: and Aims: No valid treatment or preventative strategy has evolved till date to counter the SARS CoV 2 (Novel Coronavirus) epidemic that originated in China in late 2019 and have since wrought havoc on millions across the world with illness, socioeconomic recession and death. This analysis was aimed at tracing a trend related to death counts expected at the 5th and 6th week of the COVID-19 in India. Material and methods: Validated database was used to procure global and Indian data related to coronavirus and related outcomes. Multiple regression and linear regression analyses were used interchangeably. Since the week 6 death count data was not correlated significantly with any of the chosen inputs, an auto-regression technique was employed to improve the predictive ability of the regression model. Results: A linear regression analysis predicted average week 5 death count to be 211 with a 95% CI: 1.31–2.60). Similarly, week 6 death count, in spite of a strong correlation with input variables, did not pass the test of statistical significance. Using auto-regression technique and using week 5 death count as input the linear regression model predicted week 6 death count in India to be 467, while keeping at the back of our mind the risk of over-estimation by most of the risk-based models. Conclusion: According to our analysis, if situation continue in present state; projected death rate (n) is 211 and467 at the end of the 5th and 6th week from now, respectively. Highlights: This analysis was aimed at tracing a trend related to death counts expected at the 5th and 6th week of the COVID-19 in India. If situation continue in present state; projected death rate (n) is 211 and 467 at the end of the 5th and 6th week from now, respectively. Keeping these projected mortality data in mind, current measured for containment of COVID-19 must be strengthened or supplemented.